Desenvolvimento e propriedades mecânicas da placa óssea bloqueada em formato T - Mesquita, Luciane dos Reis [UNESP] (2015)
The aim of this study was to develop a locked T-plate to be used in distal radial fractures and evaluate the mechanical properties. A titanium 2.7 mm T-plate was designed with a shaft containing three locked screw holes and one dynamic compression hole, and a head with two locked screw holes. The head of the plate had an indentation and shaft had tapered-shaped end. Forty polyurethane blocks having a T-shaped and 20 titanium T-plates were used for mechanical testing. The bone plate was positioned over the polyurethane blocks with 2 mm fracture gap between the head and shaft of the plate. Six bone-plate constructs were tested until failure, three in axial compression and three in cantilever bending, to determine the loads for fatigue testing. Fourteen bone-plate constructs were tested for failure in fatigue, seven in axial compression and seven in cantilever bending. Fatigue failure was defined as polyurethane block breakage or pullout of the screws in the polyurethane block. Tests were discontinued after one million cycles if the construct had not already failed. In both static and fatigue testing, higher values of axial compression test than cantilever bending test were observed for all variables. Moreover, the constructs under fatigue axial compression test supported a larger number of cycles to failure. The locking Tplate tested has biomechanical properties that may offer sufficient stability to resist axial loads in the treatment of a distal radius fracture